Right atrial catheter "ghost" removal by cardiac surgery: A pediatric case series report. Issue 6 (24th March 2020) - Massardier, Claire; Perron, Jean; Chetaille, Philippe; Côté, Jean‐Marc; Drolet, Christian; Houde, Christine; Vaujois, Laurence; Naccache, Lamia; Michon, Bruno; Jacques, Frédéric
Abstract: Fibrin sheath formation around long‐term indwelling central venous catheters is common and usually benign. Fibrin sheath can persist after catheter removal and rarely leads to complications. This is a report of three pediatric oncology patients that required cardiac surgery for cardiac embolization of a "ghost" catheter several years after catheter removal. One case required tricuspid valve replacement for complete tricuspid valve destruction and two had erosion through the atrial wall. The severity of these rare complications mandates follow‐up of "ghost" catheters in pediatric oncology patients.